Transformasi Pembelajaran Praktikum Tata Boga Pasca Pandemi: Studi Naratif Pengalaman Dosen Dan Mahasiswa - Ratnawati T; Muliani; Perawati Simaremare (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This narrative study explores the transformation of culinary arts practicum learning post-pandemic from the perspectives of lecturers and students. The COVID-19 pandemic forced a sudden shift from face-to-face to online learning, particularly challenging for practicum-based courses like culinary arts. This qualitative research employed narrative inquiry design, involving 4-6 lecturers and 6-8 students as participants selected through purposive sampling. Data were collected through in-depth interviews and documentation, then analyzed using thematic analysis. The findings reveal several major themes: initial shock and unpreparedness, innovation within limitations, changing roles of educators, continuous transformation, and the development of adaptability and resilience. Lecturers demonstrated creativity in adapting demonstration methods through technology, while students developed self-directed learning skills despite limited facilities. Post-pandemic, practicum learning has transformed into a hybrid model integrating technology with hands-on practice. This research contributes to understanding adaptive learning in higher education and provides recommendations for developing effective practicum curriculum in the post-pandemic era.